Strategic Rebranding Through Sensemaking and Sensegiving : The Case of a Delivery Company’s European Transformation - AL-SHEIKH ATIYE, FAISAL (My University, 2024)
Rebranding is a process in which changes are made to an already existing brand. In the mod-ern business research context, it is a common strategic that aims to increase brand equity through better alignment on what the customer expects and what the company signals to offer. The reality of a strategic rebranding process and its successful implementation can be highly complex, and to this day, the subject has received little attention in research. This study aims to provide an example of a successful rebranding process through a theoreti-cal framework of sensemaking and sensegiving. In 2022, Delivery Hero began a strategic re-branding process of bringing its different European brands under one umbrella, Foodora. The main goals of Delivery Hero’s Foodora rebranding process were organizational efficiency, differentiation from competition, and increased brand equity in crowded markets. This study shows how the company managed stakeholder involvement and faced internal and external challenges. This single case study was conducted in the spring of 2024, and it entailed qualitative semi-structured interviews with key stakeholders within the Foodora rebranding process. The analysis was based on the grounded theory approach and highlighted the importance of ef-fective leadership, clear communication, and alignment on what the customer truly wants. The findings suggest that a successful rebranding process is not only about a change in a brand’s visual identity but also requires a deeper understanding of brand identity, market positioning, and a unified strategy. Delivery Hero’s Foodora rebranding exemplifies how sensemaking and sensegiving may aid organizational change.
Keywords: brands; leadership (activity); change; branding; strategies; organisational changes; change management (leadership); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development